2020
DOI: 10.1111/tan.14120
|View full text |Cite
|
Sign up to set email alerts
|

BoLA‐DRB3 genetic diversity in Highland Creole cattle from Bolivia

Abstract: The genetic diversity of the BoLA-DRB3 gene has been reported in different cattle breeds owing to its central role in the immune response. However, it is still unknown in hundreds of cattle breeds, especially native populations. Here, we studied BoLA-DRB3 genetic diversity in Highland Creole cattle (CrAl) from Western Bolivia, raised at altitudes between 3800 and 4200 m. DNAs from 48 CrAl cattle were genotyped for BoLA-DRB3 exon 2 alleles using polymerase chain reaction-sequence-based typing (PCR-SBT). The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…Significant differences were observed in nine out of the ten native population comparisons ( p < 0.05; Table S3 ). Similar genetic distance values were observed among Holstein populations from different countries and between native breeds of Myanmar 18 , 37 .…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…Significant differences were observed in nine out of the ten native population comparisons ( p < 0.05; Table S3 ). Similar genetic distance values were observed among Holstein populations from different countries and between native breeds of Myanmar 18 , 37 .…”
Section: Resultssupporting
confidence: 79%
“…This low but significant value can be explained by high within-population diversity and differences in rare alleles profiles among them 36 . The average F ST value observed in Sudanese cattle is higher than those estimated in Myanmar native breeds ( F ST = 0.003), and slightly lower than those reported for Holstein populations from different countries ( F ST = 0.009) 18 , 37 (Fig. 5 and Table S2 ).…”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…In conclusion, we present here a new HTS system to study in parallel MHCI and DRB3 repertoires in cattle. The high number of recent publications focusing on analysis of DRB3 repertoires demonstrates the potential utility of this tool in a number of areas of research 40,42–47 . In this study, application of this system has generated novel data on the association between MHCI haplotypes and DRB3 alleles as well as generated a substantial new dataset of MHCI allele sequences and haplotype content for three major Bos indicus cattle breeds of Brazil.…”
Section: Discussionmentioning
confidence: 98%
“…24 Cattle carrying DRB3*009:02 have been seen in Japan and across the world. [43][44][45][46][47][48][49][50] On the other hands, not all cattle carrying DRB3*009:02 can be BLV ECs. Previous reports showed that minor population of cattle carrying this allele had detectable BLV provirus and progressed lymphoma.…”
Section: Discussionmentioning
confidence: 99%